Overview of Depression severity in Type 2 Diabetes Mellitus Patients at Sorong General Hospital, Southwest Papua - Dasmasela, Jhenitha Angel Maryana; Humonobe, Andrew Ivan; Asrawaty, Rosalina (Papua Medicine and Health Science, 2025)
Indonesia ranks fifth globally in the number of diabetes mellitus (DM) cases, with type 2 diabetes mellitus (T2DM) accounting for over 90%. In addition to its physical complications, T2DM is closely associated with psychological disorders, particularly depression, which often goes undetected despite its negative impact on disease management and its well-established bidirectional relationship. This study aims to describe the severity of depression among T2DM patients at Sorong General Hospital, Southwest Papua. A descriptive observational design with a cross-sectional approach was employed, involving 270 T2DM patients selected through purposive sampling based on specific inclusion and exclusion criteria. Depression severity was assessed using the Patient Health Questionnaire-9 (PHQ-9), a validated instrument for evaluating depressive symptoms. The results showed that 136 respondents (50.37%) did not experience depression, while 134 respondents (49.63%) exhibited varying degrees of depression. Among them, 102 respondents (37.78%) experienced mild depression, 30 (11.11%) had moderate depression, and 2 (0.74%) had severe depression. These findings indicate that nearly half of the respondents experienced depressive symptoms, with mild depression being the most prevalent category. The study underscores the importance of incorporating mental health assessments, such as routine depression screening, into diabetes care protocols. An integrated approach is essential to support improved clinical outcomes and enhance the overall well-being of T2DM patients.